Application of unsymmetrical bis-chalcone compounds in dye sensitized solar cell - Pan, Tze Pei; Kien, Yung Teo; Zhi-Qiang, Liu; Tsai, Jenn-Kai; Tay, Meng Guan (Elsevier B.V., 2019)
A total of nine unsymmetrical bis-chalcone compounds have been synthesized and spectroscopically characterized. The unsymmetrical bis-chaclone compounds were substituted with either methoxy (OMe) or chloro (Cl) as the electron donor, and either difluoroboryl (BF2) or a ruthenium(II)-dimethylsulfoxide [Ru(II)-DMSO] complex as the electron acceptor. All these compounds were used as the dye sensitizer in dye sensitized solar cell (DSSC) by using fluorine doped tin oxide (FTO) glass coated with titanium(IV) oxide (TiO2) as the working electrode, and the indium tin oxide (ITO) glass coated with platinum as the counter electrode. The conversion efficiency of fabricated DSSCs were tested and the unsymmetrical bis-chalcone compound with OMe and BF2 substituents in the same molecule recorded the highest efficiency at 0.091%. In contrast, the unsymmetrical bis-chalcone with OMe and Ru(II)-DMSO complex has the lowest efficiency at 0.001%.